1984
DOI: 10.1073/pnas.81.5.1385
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane biogenesis in eukaryotic cells: translocation of newly synthesized lipid.

Abstract: We examined the transfer of sterols and phospholipids from their site of synthesis to the plasma membrane of Acanthamoeba castellanii. Cells were labeled with [3H]acetate, and plasma membrane fractions were isolated under conditions that minimize the nonspecific exchange of lipids between subcellular membrane fractions. Sterols and phospholipids were purified from both whole-cell homogenates and isolated plasma membrane. In whole cells, 3H-labeled lipids were formed, with no apparent time lag, in a linear mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Most lipids are known to be synthesized in the endoplasmic reticulum (ER), but how· they are moved from there has not yet been elucidated (Bell et al 1981, Pagano & Langmuir 1983. The newly synthesized lipids could move with the proteins by vesicular traffic from the ER over the Golgi complex to the cell surface (Dower et a11982, Pfenninger & Johnson 1983, Mills et al 1984, or by transfer through the aqueous, cytoplasmic phase, possibly by binding to lipid exchange proteins (Wirtz 1974, De Grella & Simoni 1982, Yaffe & Kennedy 1983, Sleight & Pagano 1983. No studies have yet been reported on lipid traffic in epithelial cells.…”
Section: Lipidsmentioning
confidence: 98%
“…Most lipids are known to be synthesized in the endoplasmic reticulum (ER), but how· they are moved from there has not yet been elucidated (Bell et al 1981, Pagano & Langmuir 1983. The newly synthesized lipids could move with the proteins by vesicular traffic from the ER over the Golgi complex to the cell surface (Dower et a11982, Pfenninger & Johnson 1983, Mills et al 1984, or by transfer through the aqueous, cytoplasmic phase, possibly by binding to lipid exchange proteins (Wirtz 1974, De Grella & Simoni 1982, Yaffe & Kennedy 1983, Sleight & Pagano 1983. No studies have yet been reported on lipid traffic in epithelial cells.…”
Section: Lipidsmentioning
confidence: 98%
“…1) [3][4][5]. These include functioning as modulators of membrane properties (prenyllipids in archaebacteria [6] and sterols in eubacteria and eukaryotes [7]), as carriers for electron transport (menaquinone, plastoquinone, phylloquinone and ubiquinone), [8] as light harvesting and photoprotecting pigments (carotenoids, phytol side chain of chlorophyll), as regulators of growth and development (steroid hormones, gibberellins, cytokinins, abscisic acid) [9] and in signal transduction (prenylated proteins) [10]. Isoprenoids also serve as attractants for pollinators and seed dispersers [11] and as antibiotics, and herbivore repellents as well as toxins in plants [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Some eukaryotes, like Acanthamoeba, do not contain SPH, but do enrich sterols in the plasma membrane (Dawidowicz 1987), probably during vesicle transport (Mills et al 1984). It is of possible evolutionary interest that cholesterol also displays a preference for disaturated PC, close to that for SPH (Lange et al 1979;see Phillips et al 1987): the mechanism of cis Golgi sorting may originally have used disaturated phospholipids.…”
Section: (3)mentioning
confidence: 99%